New taxa and revised stratigraphic distribution of the crinoid fauna from Anticosti Island, Québec, Canada (Late Ordovician-early Silurian). (November 2019) - Ausich, William I.; Cournoyer, Mario E.
Abstract: End-Ordovician extinctions had a profound effect on shallow-water benthic communities, including the Crinoidea. Further, recovery after the extinctions resulted in a macroevolutionary turnover in crinoid faunas. Anticosti Island is the most complete Ordovician-Silurian boundary section recording shallow-water habitats. Both new taxa and changes in Anticosti Island stratigraphic nomenclature are addressed herein. New taxa include Becsciecrinus groulxi n. sp., Bucucrinus isotaloi n. sp., Jovacrinus clarki n. sp., Plicodendrocrinus petryki n. sp., Plicodendrocrinus martini n. sp., Thalamocrinus daoustae n. sp., and Lateranicrinus saintlaurenti n. gen. n. sp. The status of Xenocrinus rubus as a boundary-crossing taxon is confirmed, range extensions of several taxa are documented, and the distribution of crinoids with the revised stratigraphic nomenclature is documented. UUID:http://zoobank.org/19613a44-ec69-47d7-88ab-fcf88ba771f0 .